Religious Education and Spirituality From Student’s Perspectives In The Digital Era: Theory, Perception, And Understanding - Erly Lumban Gaol; Made Duananda Kartika Degeng; Saida Ulfa; I Nyoman Sudana Degeng (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Spirituality in education has recently become an interesting topic and discussion in the field, demanding theory, practice, and even appreciation and real action. Education in Indonesia, especially religious education and Spirituality, as early as possible becomes the foundation and dimension of life with a fragmented understanding of experience and encounters with religious traditions. This article aims to investigate students’ understandings, both theory and perception, of Spirituality and religious education in the context of education. In-depth, structured, and semi-structured interviews were conducted for 120 students using a qualitative research design. They were led in this situation by using a Google form as a lens to gauge their comprehension of the research focus. The research results have shown some points. First, Spirituality and religious education are ill-defined abstract concepts. Second, there is a correlation between Spirituality and religious instruction. Third, religion and Spirituality are like an esophagus, an oasis in the digital age. Spirituality and religious education are polarized contextually.